Species status and new distribution records for Lithurgus huberi Ducke (Hymenoptera, Megachilidae, Lithurginae) - González, Victor H. (2013)
Notes are provided on the morphology of males and females of the enigmatic Lithurgus huberi Ducke (Lithurginae: Lithurgini), a species historically believed to have been introduced into South America from Asia and to be a possible synonym of the more widespread L. atratus Smith. Distinctive differences are documented between L. huberi and L. atratus, perhaps indicative of separate species. In addition, we provide new records of L. huberi in Argentina and Paraguay.